Contributions from Dissertation Committee Members to Educational Research Training - José Margarito Jiménez Mora; María Guadalupe Moreno Bayardo; José de la Cruz Torres Frías (Universidad Nacional, Costa Rica, 2014)
This paper reflects on empirical elements derived from the work by Moreno, Torres and Jiménez (2014) entitled The Discourse of Dissertation Committee Members as a Means to Train Graduate Researchers, which is based on a research project whose object of study is the content and orientation of the messages received by doctoral education students from professors who made critical readings of their dissertation progress. This level of education was selected because practically all doctoral programs in Mexico are research oriented. Therefore, it is assumed that PhD students are trained to do research in a specific field of knowledge. Data, which was obtained from 101 reports written by 9 dissertation committee members for 60 students in two doctoral programs in education in Mexico, points out important matters that students can learn regarding how to conduct educational research and how to report it in a written text. These aspects are discussed in this paper in three areas of content, including parts of the discourse of the committee members.